Redescription of Moenkhausia megalops (Eigenmann, 1907), a widespread tetra from the Amazon basin (Characiformes, Characidae) - Soares, Isabel M. [UNESP]; Azevedo-Santos, Valter M. [UNESP]; Benine, Ricardo C. [UNESP] (Pensoft Publishers, 2017)
Moenkhausia currently comprises 90 valid species and represents one of the very species-rich genera in Characidae. Most of these species need to be revised since their original descriptions are out-of-date and are uninformative. In this sense, Moenkhausia megalops is redescribed based on the examination of the holotype and additional specimens from drainages of the Amazon basin and the type locality. The species is distinguished from its congeners by the combination of the following characters: A conspicuous bootshaped humeral spot, ventrally curved to anterior region of the body, followed by a second inconspicuous vertically elongated humeral spot; a dark longitudinal midlateral stripe on body extending from immediately posterior to the second humeral spot to the middle caudal-fin rays; a dark blotch on the upper caudal-fin lobe; and teeth with seven cusps on inner series of premaxilla and dentary.
Keywords: Astyanax megalops; Humeral spot; Moenkhausia abyss; Moenkhausia grandisquamis; Rio tapajós basin; Taxonomy